The effects of neurodynamic straight leg raise treatment duration on range of hip flexion and protective muscle activity at P1 - Neal Hanney, Ryan (J Man Manip Ther, 2016)
Study design: Randomized, single blind, same subject crossover trial. Objectives: To compare the effects of two neurodynamic treatment doses on range of hip flexion (ROM HF) and electromyographic (EMG) activity of semitendinosus, at first onset of pain (P1). Methods: A total of 26 healthy participants without low back or leg pain received each treatment in a random order with at least 48 hours between sessions. Baseline ROM HF and EMG magnitude of semitendinosus at P1 were collected. Subjects then received either 361 or 362 minutes of oscillating end of range (grade IVz) straight leg raise (SLR) neurodynamic treatment and were re-assessed for baseline measures. Results: There was no significant difference between groups in EMG magnitude (P50.190) and ROM HF (P50.739) at P1. There was also no significant difference within groups in EMG magnitude at P1 (P50.182); however, there was a significant improvement in ROM HF at P1 in both groups compared to baseline readings (P50.000), with increases of 6.7u and 5.1u for the 361- and 362-minute groups, respectively. Conclusion: Findings indicate that 362 minutes of oscillating grade IVz SLR neurodynamic treatment has no additional benefit over 361 minute, on ROM HF or EMG magnitude of semitendinosus at P1. Using an oscillating SLR treatment may, however, help to increase pain-free ROM HF, although further studies are necessary to confirm this.